The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.5398/medpet.2016.39.1.34
|View full text |Cite
|
Sign up to set email alerts
|

Egg Production and Quality of Quails Fed Diets with Varying Levels of Methionine and Choline Chloride

Abstract: The aim of the present study was to determine the effect of choline chloride supplementation at 1500 ppm in diets containing various levels of methionine on egg production and egg quality in quails. A total of 180 birds, at 6 week-old quail were divided into 18 experimental units, and assigned to a 2 x 3 factorial design experiment with 3 replications (10 birds each) in each treatment. The birds were offered diets containing choline chloride at either 0 (A1) or 1500 ppm (A2), with three levels of methionine na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 18 publications
3
6
0
1
Order By: Relevance
“…The difference in eggshell percentage may be related to the increasing percentage of another egg structure in the present case, the yolk size, since albumen percentage decreased as choline was increased, whereas eggshell thickness was not affected by the treatments. Similar results were reported by Khairani and Wiryawan (2016), who found that diets without choline supplementation lead to a higher eggshell percentage compared to choline-supplemented diets.…”
Section: Resultssupporting
confidence: 90%
“…The difference in eggshell percentage may be related to the increasing percentage of another egg structure in the present case, the yolk size, since albumen percentage decreased as choline was increased, whereas eggshell thickness was not affected by the treatments. Similar results were reported by Khairani and Wiryawan (2016), who found that diets without choline supplementation lead to a higher eggshell percentage compared to choline-supplemented diets.…”
Section: Resultssupporting
confidence: 90%
“…The feed consumption of laying quail (age of 7-11 weeks) in treatment D (15% CPF) in the diet is 21.58 g/head/day. This feed consumption was similar to that observed by Nuraini et al (2017b), who showed that the feed consumption of quails (age 7-11 weeks) in a range of 21.20-22.03 g/bird/day and higher than the results of a study by Khairani et al (2016), who found that the feed consumption of quail was 17.64-20.52 g/bird/day when fed 18% crude protein.…”
Section: Discussionsupporting
confidence: 90%
“…In terms of feed conversion, feed conversion that was not significantly different between treatment A with treatment B, C and D was due to the same feed consumption and egg mass in treatments A with, B, C and D. According Khairani et al (2016), the feed conversion ratio is the ratio between feed intakes in producing a number of eggs. Feed conversion can indicate the production coefficient; a smaller value indicates more efficient use of feed to produce eggs.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The average egg yolk scores in this study showed that the utilization of cricket meal significantly increased the score of yolk color variable. Yolk color was influenced by xanthophylls (one of two major divisions of the carotenoid group) in diet (Khairani et al, 2016). Xanthophylls give the color characteristic to the egg yolks.…”
Section: Discussionmentioning
confidence: 99%